The Effect of Usability Test for Designing M-Commerce on Customers Trust - Bin Hussain, Azham; Thamer Mahmood, Alaa; Kamil Naser, Raed; Fitri Zaaba, Zarul (International Journal of Engineering and Technology, 2018)
Usability design of any mobile application varies from one user experience to another. This depends on the highlights and attributes of structured process for any predetermined errand, for example, client trust. Existing literary works have uncovered that there is perceptible absence of concentrate on the impact of versatile or m-trade structure ease of use on clients' trust to play out specific exercises, for example, supportability, validity, content applicable and coherence. In this investigation, a nearby finished survey was disseminated among 20 m-trade clients. These clients were requested to play out some errand in order to gain some important data about client trust in m-trade. Result appeared in poll uncovered that lion's share of the members demonstrate solid enthusiasm for m-trade and have concurred that the plan convenience in driving their trust of the application is vital. The referenced ease of use components positively affected clients'' trust with the exception of supportability. Our discoveries give a few bits of knowledge to the m-business planners and engineers and expand the present comprehension about the capability of structure ease of use in driving clients' future use conduct.Â
Keywords: usability design; mobile commerce; trust; design patterns; usage behavior